Duration and Efficiency of Combined versus Isolated Aerobic Training Interventions in Post-Stroke Cognition: A Systematic Review - Reinaldo Maeneja; Inês Saraiva Ferreira; Ana Maria Abreu (Karger Publishers, 2024)
Background: This study aimed to evaluate the effects of physical activity on the cognition of patients with stroke, comparing the effectiveness of using isolated or combined rehabilitation, as well as the duration and intensity of training, to identify the characteristics of optimal training programs for post-stroke cognitive rehabilitation. Methods: For this systematic review, we followed PRISMA guidelines and searched Web of Science, Scopus, PEDRo, SPORTdiscus, PubMed, Trial Registries, and Google Scholar for studies published between 2013 and April 12, 2023. We included randomized controlled trials (RCTs) of interventions that measured the effect of physical activity on cognition in patients with stroke. We restricted our search to reports published in the English language. Evidence from the RCTs was synthesized. The risk of bias was assessed using the Cochrane risk of bias tool. Results: Of the 1,755 records identified, 34 were eligible, and data were available, with mainly low to moderate risk of general bias. The combined rehabilitation training programs proved more efficient when compared with isolated rehabilitation training programs in several cognitive domains. A moderate-intensity, 12-week intervention duration, with three weekly sessions, proved adequate. Discussion: It seems that combined rehabilitation training programs are efficient for patients with stroke as these alter neuroplastic conditions due to synergistic or additional onset of action. Future research should investigate combined rehabilitation training programs, with follow-up, to assess how long the recorded improvements last. The protocol of this study is registered in PROSPERO, number CRD42021248533.